Bactericidal and Bioactive Dental Composites - Chatzistavrou, Xanthippi; Lefkelidou, Anna; Papadopoulou, Lambrini; Pavlidou, Eleni; Paraskevopoulos, Konstantinos M.; Fenno, J. Christopher; Flannagan, Susan; González-Cabezas, Carlos; Kotsanos, Nikos; Papagerakis, Petros (Frontiers in Physiology, 2018)
Aim: Antimicrobial and bioactive restorative materials are needed to develop a bacteria free environment and tight bond with the surrounding tissue, preventing the spread of secondary caries and thus extending the lifetime of dental restorations. The characteristic properties of new dental bioactive and antibacterial composites are presented in this work. The new composites have been microstructurally characterized and both long and short term properties have been studied. Methods: The Ag-doped sol-gel derived bioactive glass (Ag-BG) was incorporated into resin composite in concentrations 5, 10, and 15 wt.%, to fabricate new Ag-doped bioactive and antibacterial dental composites (Ag-BGCOMP). The microstructural properties and elemental analysis of the developed Ag-BGCOMP was observed. The total bond strength (TBS) was measured immediately and after long term of immersion in medium using microtensile testing. The capability of Ag-BGCOMPs to form apatite layer on their surface after immersion in Simulated Body Fluid (SBF) as well as the bacteria growth inhibition in a biofilm formed by Streptococcus mutans (S. mutans) were evaluated. Results: Homogeneous distribution of Ag-BG particles into the resin composite was observed microstructurally for all Ag-BGCOMPs. The TBS measurements showed non-statistically significant difference between control samples (Ag-BG 0 wt.%) and Ag-BGCOMP specimens. Moreover, the total bond strength between the surrounding tooth tissue and the material of restoration does not present any statistically significant change for all the cases even after 3 months of immersion in the medium. The bioactivity of the Ag-BGCOMPs was also shown by the formation of a calcium-phosphate layer on the surface of the specimens after immersion in SBF. Antibacterial activity was observed for all Ag-BGCOMPs, statistically significant differences were observed between control samples and Ag-BGCOMPs. Accordingly, the number of dead bacteria in the biofilm found to increase significantly with the increase of Ag-BG concentration in the Ag-BGCOMPs. Conclusions: New resin composites with antibacterial and remineralizing properties have been manufactured. Characterization of these materials provides a rationale for future clinical trials to evaluate clinical benefits and outcomes in comparison with currently used dental materials. Significance: The new developed composites could ultimately prevent restoration failure and could advance patients' wellbeing.